Impact of Social Media on Basic School Children’s Language Achievement (Universitas Negeri Semarang, 2020)
The development of technology is increasingly rapid, teenagers are very active in using it from various sides of good and even technological workers. Part of the technology that is quite a lot of users is social media, a variety of the most widely used media such as YouTube, Instagram, Facebook, and chat applications. Plus the number of users of each social media is increasing every day. Like technology, language will also develop rapidly, language transformation will continue to move, but there are some things that need to be considered that language must also get guidance to stay good and not shift the originality of the language itself. The survey results of researchers, on some social media such as youtube and instagram, the average video maker on social media is people who follow western culture, city people, slang and even use contemporary alay language. Next too, most elementary school children use their gadgets to play games, youtube, and play Instagram. So it is deemed necessary to examine how the impact of the media on the acquisition of new language of elementary school children is studied in psycholinguistic studies.